2015
DOI: 10.5604/20831862.1163692
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treadmill exercise improves spatial memory of male appswe/ps1de9 mice by regulation of bdnf expression and microglia activation

Abstract: Increasing evidence suggests that physical activity could delay or attenuate the symptoms of Alzheimer's disease (AD). But the underlying mechanisms are still not fully understood. To investigate the effect of long-term treadmill exercise on the spatial memory of AD mice and the possible role of β-amyloid, brain-derived neurotrophic factor (BDNF) and microglia in the effect, male APPswe/PS1dE9 AD mice aged 4 months were subjected to treadmill exercise for 5 months with 6 sessions per week and gradually increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 36 publications
5
45
0
2
Order By: Relevance
“…In a recent study, a 5-months long treadmill exercise increased levels of BDNF-positive cells and spatial memory in the APPswe/PS1dE9 AD mouse model (Xiong et al, 2015). Another study has also reported increase in BDNF and improved long-term potentiation following treadmill exercise in a rat model of AD (Aβ rats) (Dao et al, 2015).…”
Section: Modulating Bdnf Signaling In the Central Nervous Systemmentioning
confidence: 99%
“…In a recent study, a 5-months long treadmill exercise increased levels of BDNF-positive cells and spatial memory in the APPswe/PS1dE9 AD mouse model (Xiong et al, 2015). Another study has also reported increase in BDNF and improved long-term potentiation following treadmill exercise in a rat model of AD (Aβ rats) (Dao et al, 2015).…”
Section: Modulating Bdnf Signaling In the Central Nervous Systemmentioning
confidence: 99%
“…We have recently shown that 6 months of voluntary running in 5xFAD mice did not result in any beneficial effects on soluble Aβ-levels, synaptic protein levels or cognitive behavior 24 . Interestingly, prior studies in other AD models suggest that exercise may reduce neuroinflammation by reducing microglial activation and levels of pro-inflammatory cytokines 31,32 . Because of its features, we view the 5xFAD model as suitable for studying the effects of exercise on neuroinflammatory and non-cognitive behavioral features of AD.…”
mentioning
confidence: 99%
“…Exercise was postulated to influence APP processing, because APP C-terminal fragments were reduced [84]. More recent studies in Tg2576 AD mice also found that exercise mitigated brain levels of Aβ 1–42 , and in APPswe/PS1dE9 mice, treadmill exercise was associated with improved spatial memory, more Brain-Derived Neurotrophic Factor (BDNF) positive cells and less activated microglia in the brain, but no change in brain Aβ [85, 86]. …”
Section: Mitochondrial Medicine and Alzheimer’s Diseasementioning
confidence: 99%